Plasmon-free SERS self-monitoring of catalysis reaction on Au nanoclusters/TiO2 photonic microarray1. Issue 42 (25th May 2015) - Qi, Dianyu; Yan, Xuefeng; Wang, Lingzhi; Zhang, Jinlong
<x xml:space="preserve">Abstract</x> Advantages of plasmon-free SERS monitoring.